Experimental Study on Axial Compression Performance of Thin-Walled Steel Tube Lightweight Concrete Columns With Composite Section - Li, Yue; Yan, Yong; Meng, Xue; Zhang, Kechao; Li, Xiaorun; Gao, Chongming (Frontiers in Materials, 2022)
In order to investigate the axial compression performance of fabricated cold-formed thin-walled steel and lightweight concrete composite columns, the axial compression tests were conducted on single-limb and double-limb specimens and compared with hollow specimens to analyze the effects of various factors such as cross-sectional size of the members, wall thickness of the sections and steel content on the axial compressive load capacity of the members. The test results show that： (1) Under the axial load, the typical damage of fabricated cold-formed thin-walled steel and lightweight concrete composite column is local buckling of the steel tube and local crushing of the concrete. (2) The ultimate bearing capacity of thin-walled steel double-limb composite column is the highest. When the specimen aspect ratio L/D is 1.43, the ultimate bearing capacity of single-limb column is 114.17% higher than that of empty steel tube. The ultimate bearing capacity of double-limb column is 275.71% higher than that of empty steel tube. (3) Based on the material superposition strength theory, the calculating method of the load bearing capacity of fabricated cold-formed thin-walled steel composite columns is proposed. The formula for calculating the ultimate load capacity applicable to the composite columns is verified after comparing with the test results, which provides the guidance for the design of such members.